Penentuan Indeks Seleksi Toleransi Kekeringan Galur Dihaploid Padi Sawah Tadah Hujan pada Fase Perkecambahan - Akbar, Miftahur Rizqi; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Suwarno, dan Willy Bayuardi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Rainfed rice tolerant to drought and high yielding would be an alternative to rainfed lowland areas prone to drought stress. Selection in the early phase of plant growth will accelerate the effort to obtain rainfed varieties. The objective of this experiment was to identify characters that significantly affect the selection of drought tolerance using PEG 6000 concentration of 25% in the germination phase. The experiment was conducted in greenhouse of ICABIOGRAD, Bogor, using a factorial randomized complete block design with three replications. The first factor was 32 rice genotypes while the second factor was 2 levels of PEG 6000, i.e., concentrations of 0 and 25%. The results showed that the correlation analysis and principal component analysis obtain the important characters namely the germination percentage, seminal root length, and the dry weight of seminal roots. Based on discriminant analysis, the index matching value of 96.77% was suitable to distinguish tolerant and sensitive genotypes using PEG 6000 concentration of 25% in the germination phase.